Factors associated with dental clinic use by clients in Nigeria during the COVID-19 pandemic - Yewande Isabella Adeyemo; Mahsa Karimi; Elizabeth Oziegbe; Bamidele Olubukola Popoola; Michael Alade; Ahmad Reza Shamshiri; Heikki T. Murtomaa; Tosin Olajide Oni; Joycelyn Odegua Eigbobo; Nneka Kate Onyejaka; Olubukola Olamide Olatosi; Chioma Love Nzomiwu; et al. (BMC Oral Health, 2024)
Abstract Background Nigeria, like many other countries, faced challenges in dental care provision during the COVID-19 pandemic, necessitating limited care to emergencies only. However, the impact of restricted access to dental services on oral health remains a concern, particularly w﻿ith preventive maintenance care. This study aims to identify the factors associated with dental service utilization during the COVID-19 pandemic among patients attending dental clinics in Nigeria, and their sources of information about COVID-19. Methods This cross-sectional study recruited 500 participants who had visited dental clinics before and during the pandemic. Data were collected through telephone interviews and online questionnaires betw﻿een September and December 2021. Inferential analyses were conducted using ordered logistic regression models to assess the association between the independent (awareness of emergency dental treatments, knowledge of COVID-19 transmission routes in dentistry, awareness of required preparations in dental practice settings, fear of COVID-19 infection in dental settings), and dependent (utilization of dental services during the pandemic) variables after adjusting for confounding variables (age, sex, educational status, COVID-19 vaccinations status and COVID-19 status of live-in residents). The sources of COVID-19 information by dental patients was also identified. Statistical significance was established at 95% confidence level with a p value < 0.05. Results Many participants were males (51.2%) and had tertiary education (61.6%). Fear of COVID-19 infection in dental settings was significantly associated with lower odds of utilizing dental care services during the pandemic (Adjusted Odds Ratio: -0.06, 95% Confidence Interval: -0.08, -0.01). The main sources of COVID-19 information were mass media and social networks, with only 42% receiving information from dental professionals. Conclusion Fear of COVID-19 infection in dental settings significantly influenced dental service utilization during the pandemic. Strategies to address fear and improve communication channels between dental professionals and patients are essential for promoting oral health during similar crises.